Lomofungin, an Inhibitor of Ribonucleic Acid Synthesis in Yeast Protoplasts: Its Effect on Enzyme Formation - Kuo, S.-C. (1973)
Lomofungin, an antibiotic active against fungi, yeasts, and bacteria, rapidly inhibits synthesis of ribonucleic acid (RNA) but not protein by protoplasts of Saccharomyces strain 1016. With 40 μg of lomofungin/ml, RNA synthesis was almost completely halted after 10 min of incubation; protein synthesis continued for at least 40 min. Since lomofungin inhibits isolated RNA polymerases from yeast, but not in vitro protein synthesis, it is concluded that the primary action of lomofungin in yeast protoplasts is on RNA synthesis. Examination of the pulse-labeled RNA indicated that biosynthesis of both ribosomal precursor RNAs and messenger RNAs was severely inhibited after the protoplasts were incubated with lomofungin for 5 min, whereas formation of small-molecular-weight RNA (4 to 5s) was only slightly affected. Under these conditions, lomofungin almost completely prevented induction of α-glucosidase. Once the protoplasts had been induced, further production of the enzyme was not impaired by lomofungin until after 30 min of incubation, but was rapidly halted by cycloheximide (4 μg/ml). Lomofungin inhibition of invertase formation by protoplasts actively synthesizing the enzyme also became evident only after a lag of about 30 to 40 min, although synthesis was promptly halted by cycloheximide. These observations suggest the existence of relatively long-lived specific messenger RNAs for these enzymes.